A new coronavirus infection: aspects of complex comorbidity - V. V. Shkarin; O. V. Kovalishena; A. A. Murtayeva; A. V. Sergeeva (Эпидемиология и вакцинопрофилактика)
Relevance. Currently, there is a significant increase in the combination of infectious and non-infectious pathology. as well as increasing the attention of researchers to this problem. The purpose. of this article is to review scientific data on the combination of the new coronavirus infection COVID-19 with infectious and non-infectious pathology and to assess the phenomenon of complex comorbidity in relation to this new infection. Results. It was found that patients 60 years and older - all have complex comorbidity, which increases the risk of death by more than 7 times, and the presence of two or more comorbid diseases in patients compared with patients who had no more than one disease, the risk of death increased by 9 times. Conclusion. A high potential of combination with COVID-19 is shown, primarily with tuberculosis, HIV infection, hepatitis B and C, as well as with a large group of opportunistic infections.